Using Multivariate Analysis To Classify Traditional Private Banks Operating In Syria According To Financial Performance Indicators - احمد, طالب; ضاهر , حنان; خيربك, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of this research is to apply one of the multivariate statistical analysis methods in order to know the disparity in the values ​​of financial indicators in the traditional private banks operating in Syria, which is the cluster analysis in order to distinguish the financial indicators that appear in a way that notices this disparity, and the results showed the lack of homogeneity in private traditional banks. operating in Syria in relation to the values ​​of financial indicators, and it was found that the traditional private banks operating in Syria can be classified through the method of cluster analysis into three clusters (the first cluster banks with low-value indicators: Arab Bank, Swiya and Gulf Bank), (the second cluster banks with medium indicators) Value: Bank of Syria and Overseas, Bank of Commerce and Finance, Bank Audi, Fransabank, Bank of Jordan, Bank Bemo, Bank Al-Sharq, Byblos Bank), (the third cluster of banks with high-value indicators: Qatar), and the results of the analysis showed that the variables (capital adequacy ratio Money), (total risks to total assets), (equity to assets), (default ratio), (return on assets), (equity to liabilities), have a significant impact on the classification of private conventional banks working in Syria. *Associate Professor, Statistics and Programming Department - Faculty of Economy, Tishreen University –Latakia- Syria.